TeenyLIME: Transiently Shared Tuple Space Middleware for Wireless Sensor Networks - Costa, Paolo; Mottola, Luca; Murphy, Amy L.; Picco, Gian Pietro (The 1st International Workshop on Middleware for Wireless Sensor Networks (MidSens 2006), co-located with ACM Middleware'06, Melbourne, Australia., 2006)
Recent developments in wireless sensor networks (WSNs) are pushing scenarios where application intelligence is no longer relegated to the fringes of the system (i.e., on a data sink running on a powerful node) rather it is distributed within the WSN itself. To support this scenario, we propose , a tuple space model and middleware supporting applications where sensing and acting devices themselves drive the network behavior. In other words, the application core is not confined to the powerful sinks, rather it is deployed on the devices embedded within the physical world. Tuple space operations are used both for data collection as well as to effect coordination among sensing and acting devices. This paper describes the model and corresponding middleware implementation.